Permeability Characteristics of Water-Sand Seepage in Fracture by Experiment - Yu Liu; Shuncai Li; Wei Li; Zhihao Luo; Liming Wu; Zhipeng Xu (Advances in Civil Engineering)
Studies on the seepage characteristics of water-sand cracks are of great significance to reveal the mechanisms of water and sand inrush. Using a self-made water-sand fracture seepage test instrument, a water-sand seepage test was carried out, and the permeability of water and sand in the fracture was determined. The hysteresis characteristics of water-sand flow in the fracture were obtained after the required permeability was attained. The results show that the hysteresis curve changes from type I to type IV with the increase in sand particle size and concentration. The hysteresis parameters are described by the maximum hysteresis Gp∗ and the hysteresis area S, both of which show an increasing trend with the increase in sand particle size and concentration; however, this increase is not synchronous. The average velocity and turbulent kinetic energy distribution of the water-sand fluid on the fracture cross section are greatly affected by the particle size and concentration of the volume of sand. This study can provide a reference for further study of water inrush from a shallow coal seam. Through simulation, it is found that the particle size has a great influence on the seepage velocity, and the influence near the side wall surface is greater than that in the middle position.